(untitled) (Applied Biological Research, 2023)
The present study was aimed to assess the methanolic extracts of Gracilaria corticata and G. foliifera for anti-proliferative and anti-oxidant potency against breast cancer cell line MDA-MB-231. The antitumor activity of G. corticata methanolic extract (GCME) and G. foliifera methanolic extract (GFME) against MDA-MB-231 cells was assessed by 3- (4,5-dimethylthiazol-2-cyl)-2,5-diphenyltetrazolium bromide (MTT) assay. The extracts decreased cell viability of MDA-MB-231 cells with an estimated half-maximal inhibitory concentration (IC50) of 0.18 ± 1 and 0.078 ± 1 for GFMEs; and 0.116 ± 1 and 0.107 ± 1 for GCMEs. GCME significantly increased ROS level after 48 h of treatment and decreased glutathione (GSH) level (p<0.01) in a dose-and time-response manner. Intracellular ROS in MDA-MB-231 cells was determined by staining with fluorogenic agent 2′,7′-dichloro-dihydrofluorescein diacetate (H2DCFDA). The mitochondrial membrane potential (Δψm) disruption of GFME and GCME treated cells were maximum at 0.078 and 0.107 μg μL-1(p<0.005). G. foliifera showed significantly higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity (78.6%) as compared to G. corticata (68.3%). This study also explored the phytochemical constituents of GFME and GCME such as hexadecanoic acid, methyl ester and cholesta 4,6-dien-3-ol, (3 beta), through GC-MS analysis.